Prevalence of Severe Acute Respiratory Syndrome Coronavirus 2 Antibodies Among Market and City Bus Depot Workers in Lima, Peru. (21st April 2021) - Tovar, Marco; Peinado, Jesús; Palomino, Santiago; Llanos, Fernando; Ramírez, Claudio; Valderrama, Gisella; Calderón, Roger I; Williams, Roger B; Velásquez, Gustavo E; Mitnick, Carole D; Franke, Molly F; Lecca, Leonid
Abstract: We report severe acute respiratory syndrome coronavirus 2 antibody positivity among market and city bus depot workers in Lima, Peru. Among 1285 vendors from 8 markets, prevalence ranged from 27% to 73%. Among 488 workers from 3 city bus depots, prevalence ranged from 11% to 47%. Self-reported symptoms were infrequent.